Pengaruh Celebrity Endorser Produk Sayurbox terhadap Minat Beli Konsumen - Khairunnisa, Nadia Maulida; Mirajiani, Mirajiani; Astuti, Andjar; Setiawan, Johan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2024)
This research aimed to determine the effect of attractiveness, trustworthiness, and expertise owned by celebrity endorser on consumer buying interest partially and simultaneously. Data collection used the questionnaire method with 486 thousand population and with the provisions of researchers that have been considered, then obtained as many as 50 samples. The analysis of the data that has been obtained in the form of quantitative analysis, including validity test, reliability test, through t test and F test to prove the hypothesis, determination coefficient analysis test (R2), and classical assumption test. This study used multiple linear regression analysis which aims to see the influence between variables. Hypothesis test analysis (t test) showed attractiveness has a sig value of 0.026 < 0.05, trustworthiness has a sig value of 0.977 > 0.05, expertise has asig value of 0.000 < 0.05. The t test resulted one of the variables, trustworthiness, can not significantly affect consumer buying interest. The F test analysis showed a sig value of 0.000 < 0.05, meaning that the three variables simultaneously or together proved to have a positive and significant effect on consumer buying interest.